A comparison of perennial ryegrass‐ and tall fescue‐based swards with or without a cropping component for dairy production: Animal production, herbage characteristics and financial performance from a 3‐year farmlet trial. (3rd December 2017) - Lee, J. M.; Clark, D. A.; Clark, C. E. F.; Waugh, C. D.; Roach, C. G.; Minneé, E. M. K.; Glassey, C. B.; Woodward, S. L.; Woodfield, D. R.; Chapman, D. F.
Abstract: Perennial ryegrass/white clover swards have some limitations in temperate grazed dairying systems. This study tested the hypothesis that farmlets based on alternative species would be equally or more profitable than those perennial ryegrass‐based, and would produce more herbage in summer‐dry conditions. Six farmlets were established; three with perennial ryegrass‐ and three with tall fescue‐based swards. For each grass species, one farmlet was solely based on grass‐clover swards while the other two had either chicory‐red clover or lucerne crops planted on 20%–25% of the area. Animal‐ and herbage performance‐related variables were measured for 3 years, and calculated financial performance was evaluated. Using tall fescue improved total annual herbage yield compared with perennial ryegrass, but animal production and operating profit were lower. This was likely due to the reduced yield and nutritive value of tall fescue during spring and an associated decline in daily milksolids production. The deficit in spring milksolids production was never recovered, despite greater herbage production from tall fescue during summer/autumn. Incorporating chicory‐red clover or lucerne crops reduced both annual herbage and milksolids production. This reduced farm income, while increasing operating expenses as the farmlets required crop renewal and more purchased supplementary feed to maintain feed supply. Under the conditions of this study (i.e., partial irrigation, high nitrogen supply), changing the forage base from perennial ryegrass to tall fescue did not improve animal production or profitability, nor did incorporation of crops on 20%–25% of the farmlet area.